2020
DOI: 10.1101/2020.05.05.20092254
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

County-level factors influence the trajectory of Covid-19 incidence

Abstract: With new cases of Covid-19 surging in the United States, we need to better understand how the spread of novel coronavirus varies across all segments of the population. We use hierarchical exponential growth curve modeling techniques to examine whether community social and economic characteristics uniquely influence the incidence of Covid-19 cases in the urban built environment. We show that, as of May 3, 2020, confirmed coronavirus infections are concentrated along demographic and socioeconomic lines in New Yo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 16 publications
(21 reference statements)
0
7
0
2
Order By: Relevance
“…It is widely established that social determinants of health lead to health inequities, [39][40][41][42] and our findings are consistent with recent literature describing health disparities in COVID-19. [43][44][45] Socioeconomic status is also associated with other underlying comorbidities that may heighten vulnerability to COVID-19 infection and mortality such as hypertension, obesity, renal disease, heart disease, and diabetes. [46][47][48][49] Moreover, the ability to stay-at-home and physically distance are not only considerably more difficult in those engaged in essential work, but also in those with other adverse social determinants such as food insecurity, 17,18 unstable housing, 19,20 or experiencing domestic violence.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely established that social determinants of health lead to health inequities, [39][40][41][42] and our findings are consistent with recent literature describing health disparities in COVID-19. [43][44][45] Socioeconomic status is also associated with other underlying comorbidities that may heighten vulnerability to COVID-19 infection and mortality such as hypertension, obesity, renal disease, heart disease, and diabetes. [46][47][48][49] Moreover, the ability to stay-at-home and physically distance are not only considerably more difficult in those engaged in essential work, but also in those with other adverse social determinants such as food insecurity, 17,18 unstable housing, 19,20 or experiencing domestic violence.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the history of this reemerging song and its place in the social life in the studied borderscape, I checked my assumptions with Marino Kranjac and Dario Marušić, two of the leading figures of the Istrian folk revival movement. They confirmed that the song was very well known in northern Istria among both Slovenes and Croats and was sung by these two and Italians (Kranjac, 2022;Marušić, forthcoming). When performed by choirs and folk revival groups, such as Šavrinske pupe en ragaconi, each chose its selection of verses.…”
Section: The Istrian Variantsmentioning
confidence: 64%
“…When performed by choirs and folk revival groups, such as Šavrinske pupe en ragaconi, each chose its selection of verses. Kranjac also made a selection of verses in Slovenian, Italian, and Croat dialects and performed them with Vruja group with instrumental accompaniment in a dance rhythm, with the rhythmic pattern derived from the balun or balon dance (Kranjac, 2022). The song without instrumental accompaniment and with the first stanza preserved is still sung spontaneously by older people in Slovenian Istria, whether at home, in the osteria, in the canteen, or at other gatherings (ibid.).…”
Section: The Istrian Variantsmentioning
confidence: 99%
“…Jurja. 22 Njegova je teza: Opatija sv. Jurja kraj Senja je postojala, ali ne na području današnjeg Sv.…”
Section: Abatovounclassified
“…117 CD VII, 81.118 Ugrin "cum consensu et voluntate comitis Leonardi et comitis Bartoli nepotis sui" daruje franjevcima vrt "prope locum fratrum minorum de Segnia". (CD VII,(21)(22)(23)(24)(25)(26)(27)(28)(29) 119 Godine 1350., 2. ožujka. "Elizabet relicta olim bone memorie domini comitis Duymi" daruje "ecclesiae fratrum minosrum de Segnia unan domum … quam domum domina Elena genitrix dicte domine Elizabet, olim Croatorum banissa eidem ecclesiae in suo testamento legavit" (CD XI, 584-585).120 CD XII, 217.njegovih nasljednika 30 solida.…”
unclassified